Rupturas moleculares emancipatórias: a potencialidade da prática do serviço social - Luiz, Danuta Estrufika Cantoia (2005)
This study aims at analyzing the potentiality of the Social Work practice to produce emancipatory molecular ruptures in the context of Qualification Programs for Municipal Councilors of Social Assistance in the State of Paraná. Based on Gramsci s theoretical fundamentals we argue the necessity of qualification and strengthening of these social subjects through the elevation from the common sense to the self-constitution of a critical conscience and consequent stimulation of their social and political performance considered as emancipatory molecular rupture in order that such can contribute to the construction of an anti-hegemony to the instrumental rationality that follows the modern society. Conferring materiality to this analysis, the research s support is the critic to the hegemonic and contradictory class-nature of the modern society, in what we search for the fundamentals and critical-modern values of social emancipation while process that develops the critical knowledge and reason and the social and politic performance of groups, organizations and segments of subaltern classes to support the necessity of enlargement of the participative democracy and the expansion of the modern public space, as one of the alternatives to revert the hegemonic scenario. Aiming at facing the hegemonic tendency for passive acceptance of the rationality of modern social practices, in the thesis, we argue that the Modernity contradictory historical scenario that determines social practices development also establishes an emancipatory reason, not above the humans, but as conquest and outcome of its daily fights, that needs to be developed in the most professional and social practices in a sense of contributing to the construction of a new culture for the subaltern class. Such principle carries as presupposition that Social Work can develop, in its professional practice instance, actions that move molecular ruptures face to the hegemonic perspective and that contribute to give procedural instruments to municipal councilors for this social undertaking. In order to corroborate such presupposition, it was necessary the appealing to the representative subjects (social workers and qualified councilors) of the practice developed in the Qualification Programs, focused on a theoretical-critical base, what validated the presupposition that moves the present thesis, systematizing and characterizing a professional practice, through the recovery of fundamentals, values, actions, goals and marks that demonstrate the ethic-political and practical commitment of the profession with the social emancipation